Organosulfur and phenolic content of garlic (Allium sativum L.) and onion (Allium cepa L.) and its relationship with antioxidant activity - Soto Vargas, Verónica Carolina; Gonzalez, Roxana Elizabeth; Sance, Maria Marta; Galmarini, Claudio Romulo (2018)
VII International Symposium on Edible Alliaceae